(untitled) (Research, Society and Development, 2022)
Introduction: Overdiagnosis is characterized by the unnecessary diagnosis of pathologies in asymptomatic patients through screening programs or routine exams, a pathology that would not lead to serious symptoms or death. Objective: To review the literature on Overdiagnosis in the context of cancer and how this practice impacts the lives of patients, as well as the health system and public spending. Methods: An integrative review of the literature on Overdiagnosis in the context of cancer carried out in the LILACS, SCIELO, MEDLINE and PubMED databases from January to May 2021, with full and original articles selected in Portuguese, English and Spanish. Results: 24 articles were selected that address the issue of Overdiagnosis in the context of prostate, breast, thyroid, lung and bowel cancer. Conclusion: The studies show the impact of Overdiagnosis in the early diagnosis of cancer, a fact that directly affects the psychological health of the patient and the expenses of the health system. There is a need for further research in order to find new ways of screening for cancer to reduce the risks to the health of the population and redirect the government budget to really necessary situations.